COVID-19 related health inequality exists even in a city where disease incidence is relatively low: a telephone survey in Hong Kong. Issue 7 (5th January 2021) - Chung, Roger Yat-Nork; Chung, Gary Ka-Ki; Marmot, Michael; Allen, Jessica; Chan, Dicken; Goldblatt, Peter; Wong, Hung; Lai, Eric; Woo, Jean; Yeoh, Eng-Kiong; Wong, Samuel Y S
Abstract : Background: We examined whether COVID-19 could exert inequalities in socioeconomic conditions and health in Hong Kong, where there has been a relatively low COVID-19 incidence. Methods: 752 adult respondents from a previous random sample participated in a telephone survey from 20 April to 11 May 2020. We examined demographic and socioeconomic factors, worry of COVID-19, general health, economic activity, and personal protective equipment (PPE) and related hygiene practice by deprivation status. The associations between deprivation and negative COVID-19 related issues were analysed using binary logistic regressions, while the associations of these issues with health were analysed using linear regressions. Path analysis was conducted to determine the direct effect of deprivation, and the indirect effects via COVID-19 related issues, on health. Interactions between deprivation and the mediators were also tested. Results: Deprived individuals were more likely to have job loss/instability, less reserves, less utilisation and more concerns of PPE. After adjustments for potential confounders, being deprived was associated with having greater risk of low reserve of face masks, being worried about the disease and job loss/instability. Being deprived had worse physical (β=−0.154, p<0.001) and mental health (β=−0.211, p<0.001) and had an indirect effect on mental health via worry and job loss/instability (total indirect effect: β=−0.027, p=0.017; proportion being mediated=11.46%). In addition, significant interaction between deprivation and change of economic activity status was observed on mental health-related quality of life. Conclusion: Even if the COVID-19 incidence was relatively low, part of the observed health inequality can be explained by people's concerns over livelihood and economic activity, which were affected by the containment measures. We should look beyond the incidence to address COVID-19 related health inequalities.